2000
DOI: 10.1101/gad.842500
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for Atr in phosphorylation of Chk1 and cell cycle regulation in response to DNA replication blocks and UV-damaged DNA in Xenopus egg extracts

Abstract: The checkpoint kinase Xchk1 becomes phosphorylated in Xenopus egg extracts in response to DNA replication blocks or UV-damaged DNA. Xchk1 is also required for the cell cycle delay that is induced by unreplicated or UV-damaged DNA. In this report, we have removed the Xenopus homolog of ATR (Xatr) from egg extracts by immunodepletion. In Xatr-depleted extracts, the checkpoint-associated phosphorylation of Xchk1 is abolished, and the cell cycle delay induced by replication blocks is strongly compromised. Xatr fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
373
1
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 405 publications
(389 citation statements)
references
References 60 publications
14
373
1
1
Order By: Relevance
“…ATM becomes activated in response to DNA lesions or perhaps by alterations in chromatin structure through intermolecular autophosphorylation on Ser1981 (Bakkenist and Kastan, 2003). On the other hand, ATR regulates the cellular response to ultraviolet (UV) radiationinduced damage and stalled DNA replication forks and also participates in the late response to IR (Tibbetts et al, 1999;Guo et al, 2000). Activation of ATR proceeds through its association with ATR-interacting protein (Cortez et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…ATM becomes activated in response to DNA lesions or perhaps by alterations in chromatin structure through intermolecular autophosphorylation on Ser1981 (Bakkenist and Kastan, 2003). On the other hand, ATR regulates the cellular response to ultraviolet (UV) radiationinduced damage and stalled DNA replication forks and also participates in the late response to IR (Tibbetts et al, 1999;Guo et al, 2000). Activation of ATR proceeds through its association with ATR-interacting protein (Cortez et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorylation, stabilization, and activation of p53 are accomplished at least in part by members of the replication checkpoint, namely the PI3K-like protein kinase ATR (Ataxia telangiectasia mutated (ATM) and Rad3 related) 13,14 and its substrate checkpoint kinase 1 (Chk1), 15 which have been shown to play a major role during the elimination of cultured cells in response to DNA damage and replication blocks. [16][17][18][19][20] Studies with Xenopus egg extracts have further demonstrated that immunodepletion of Pold leads to an increase in the phosphorylation of Chk1. 5 Together, this suggests that disruption of Pold might lead to the activation of the replication checkpoint and downstream effectors like p53 via the function of ATR.…”
Section: Introductionmentioning
confidence: 99%
“…An SQ/TQ domain (residues 317-383) contains putative phosphorylation sites for ATM/ATR and lies within the regulatory domain. Chk1 is phosphorylated on Ser317 and Ser345 in response to replication stress or other types of DNA damage in an ATM/ATR-dependent fashion [16][17][18][19][20]. To determine which part of the Chk1 protein is required for DNA damage-induced Chk1 nuclear localization and retention, we generated fusion proteins by attaching GFP in-frame at the C-terminus of Chk1 mutants missing different parts of the regulatory domain.…”
Section: Discussionmentioning
confidence: 99%
“…ATM phosphorylates Ser317 and Ser345 of Chk1 in response to DNA damage. There is a nuclear location sequence (NLS) in motif 260-271 of Chk1 ( Figure 1) [16][17][18][19][20][21]. In yeast and mammalian cells Chk1 is located both in the cytoplasm and nuclei before DNA damage, but it accumulates in nuclei after DNA damage, indicating a distinct change in subcellular location [22].…”
mentioning
confidence: 99%